الضمانات القانونية لعمل الأسر المنتجة في النظام السعودي - بن محمد غازي المارية, عمرو (University of Eloued جامعة الوادي, 2019)
تأتي برامج الأسر المنتجة كأحد الخيارات المطروحة بقوة للتخفيف من حدة الفقر والبطالة، لذا فقد أولت الدولة هذا الجانب عنايتها واهتمامها؛ وليس أدل على ذلك من إصدار اللائحة التنظيمية لعمل الأسر المنتجة، ويحاول هذا البحث إلقاء الضوء على موضوع الضمانات القانونية لعمل الأسر المنتجة، بغية الإجابة على سؤال رئيس وهو مدى توافر ضمانات قانونية في اللائحة التنظيمية لعمل الأسر المنتجة السعودية الجديدة، تساعد في تنظيم أوضاع الأسر المنتجة وتحقق حماية فاعلة لها The programs of productive families come as one of the options that are strongly suggested to alleviate poverty and unemployment. Therefore, the State has given this aspect its attention and concern, And the evidence on this is issuing the organized regulations governing the work of productive families. This research attempts to shed light on the issue of legal guarantees for the work of productive families to answer the main question of the availability of legal guarantees in the organized regulation of the work of the new productive families of Saudi Arabia, helping to regulate the situation of productive families and achieve effective protection for them.
مجلد3، عدد1
Keywords: المشاريع الصغيرة- الإنتاج المنزلي- الصناعات الصغيرة- الحرف البيئية- الأسر المنتجة